PELATIHAN PEMBUATAN SOKET KAKI PALSU MENGGUNAKAN BAHAN BAHAN KOMPOSIT SERAT BAMBU - Agustinus Purna Irawan; I Wayan Sukania; Paula T. Anggarina (Jurnal Bakti Masyarakat Indonesia, 2021)
Indonesia is a country rich in natural fibers. Natural fibers have the potential to be developed further into alternative products that are beneficial for the welfare of society. Natural fibers, including bamboo, hemp and rattan, have the potential to be developed into cheap, strong, safe, and comfortable biomaterials. One product that can be developed based on natural fiber composites is a prosthetic leg socket. In this community service activity, manufacturing technology use to build prosthetic sockets includes the usage of bamboo fiber composite materials and an epoxy matrix. One of the Community service activities carried out is the training for Small and Medium Enterprises engaged in the manufacture and marketing of prosthesis products, to produce socket prostheses using epoxy bamboo fiber composite materials. Through this activity, it is hoped that the appropriate technology that has been obtained through research activities funded by the Higher Education research grant, can be more beneficial for Small and Medium Enterprises and be used in the production process of socket prostheses which are cheaper, stronger, environmentally friendly and made with materials which are still abundant. Based on the results of these community service activities, some training has been given to Small and Medium Enterprises so that they can produce prosthetic leg sockets made of bamboo fiber composite material.ABSTRAKIndonesia adalah negara yang kaya dengan serat alam. Serat alam berpotensi untuk terus dikembangkan menjadi produk alternatif yang bermanfaat bagi kesejahteraan masyarakat. Serat alam antara lain bambu, rami dan rotan, sangat berpotensi untuk dikembangkan menjadi biomaterial yang murah, kuat, aman, dan nyaman. Salah satu produk yang dapat dikembangkan berbasis komposit serat alam adalah soket kaki palsu. Pada kegiatan pengabdian pada masyarakat ini, diimplementasikan teknologi manufaktur pembuatan soket kaki palsu dengan menggunakan bahan komposit serat bambu dan matriks epoksi. Kegiatan pengabdian pada masyarakat yang dilaksanakan adalah pelatihan kepada UMKM yang bergerak di bidang pembuatan dan pemasaran produk prosthesis, untuk memproduksi soket prosthesis dengan menggunakan bahan komposit serat bambu epoksi. Melalui kegiatan ini, diharapkan teknologi tepat guna yang telah diperoleh melalui kegiatan penelitian yang dibiayai oleh hibah penelitian Dikti, dapat lebih bermanfaat bagi Usaha Kecil dan Menengah dan digunakan dalam proses produksi soket prosthesis yang lebih murah, kuat, ramah lingkungan dan bahan yang melimpah. Berdasarkan hasil kegiatan pengabdian kepada masyarakat, telah diberikan pelatihan kepada Usaha Kecil dan Menengah, sehingga dapat memproduksi soket kaki palsu dari bahan komposit serat bambu